PENINGKATAN GENETIK PADA PEMULIAAN Melaleuca cajuputi subsp. cajuputi - Mudji Susanto; Anto Rimbawanto; Prastyono Prastyono; Noor Khomsah Kartikawati (Jurnal Pemuliaan Tanaman Hutan, 2008)
The breeding program of Melaleuca cajuputi subsp. cajuputi in Indonesia  was started  in 1994 by the Institute for Biotechnology and Forest Tree Improvement in cooperation  with CSIRO-Australia. An assessment  of progeny test of M. cajuputi at Paliyan at  23 months and at Sukun-Ponorogo at 36 months old were conducted to ascertain the  patterns of genetic variation in growth and foliar oil   and to  estimate genetic parameters in growth and foliar oil .  Based on the evaluation, genetic variation on growth and oil yield were high. Genetic gain estimation for growth and oil yield were 11.83 to 20.38 % in the progeny test seedling seed orchard of M. Cajuputi at Sukun, Ponorogo.